PENGARUH PENYELARASAN STRATEGIK TERHADAP KINERJA ORGANISASI ( Studi Empiris pada Rumah Sakit dan Klinik di Pangkalan Bun, Kalimantan Tengah ) - Putu Handoko Murti; Sudarno Sudarno (Diponegoro Journal of Accounting, 2014)
This study aims to examine the effect of strategic alignment on organizational performance at Pangkalan Bun’s hospital and clinics, Central Kalimantan. The performance of an organization is a factor that determines how the existence and competitiveness of an enterprise. Good performance of the organization is an organization which capable of aligning business strategy and IS/IT strategy. Using survey data from middle management and top management with data collection of responder by post. The analytical tool is used Partial Least Square based on Structural Equational Modelling And SmartPLS software. Result of this research is that the organization's performance is influenced by strategic alignment, business strategy and IS/IT strategy. Meanwhile strategic alignment is influenced by business strategy and IS/IT strategy. Thereby can be concluded that organizational performance is still affected by the alignment between business strategy and IS/IT strategy.